Besarnya Gaya Gerak Listrik (GGL) Induksi Yang Dihasilkan Oleh Generator Sebagai Pembangkit Listrik Untuk Kebutuhan Pabrik Di PT. Z - Karti Karti (CV MEDAN TEKNO SOLUSI, 2023)
A generator is a device capable of producing electric current. one type of generator is an alternating current generator. Alternating current generators function to convert mechanical power into alternating current electric power. This tool is often used in industry to drive several machines that use electric current as a driving source. The method used is the interview and observation method where questions and answers are asked directly with employees or field supervisors about the power generated by the generator used in the factory and direct observation in the field of the object to be studied. Because of the potential difference between points a and b so that electricity from a flows to b so that a physical phenomenon called electromotive force (GGL) induction occurs, where electromotive force is the force acting on electric charges moving in an electric field or magnetic field. This force refers to the force or impetus that affects the movement of electric charges in a particular medium. From the results of the calculation, the results of the induced electromotive force (GGL) generated by the generator are: E = 342,51 V. And for the results of the calculations obtained the results of the Emax electromotive force (GGL) induction generated by the generator, namely: E_max = 638,06 V. There are several factors that affect electromotive force including: The speed of change in the magnetic field, the number of turns, and the strength of the magnet.